Instalasi Perangkat Media Informasi Digital di SDIT Saad Bin Abi Waqqash Kecamatan Kediri Kabupaten Lombok Barat - Syafaruddin Ch; Suthami Ariessaputra; Budi Darmawan; Paniran Paniran; Cahyo Mustiko Okta Muvianto (Jurnal Gema Ngabdi, 2026)
Advances in information technology have driven the use of digital media as a more effective means of conveying information in educational settings. However, SDIT Saad Bin Abi Waqqash does not yet have a digital information system capable of delivering information to the school community quickly and dynamically. This community service project aims to design and implement a digital information board system with a running-text display suitable for the school environment. The method used is an action research approach, which includes the identification, planning, implementation, and evaluation stages. The planning process involves determining the installation location based on the building’s layout and designing an LED dot-matrix system. The implementation results show that the running text system operates effectively, displays information in real time, and provides optimal visibility from various areas of the school. Additionally, the developed system is easy for users to operate via a smartphone-based application. Thus, the use of running text as a digital medium for information dissemination can enhance its effectiveness and support the use of technology in the school environment.